INTERNALIZATION OF RELIGIOUS AND SOCIAL VALUES IN THE FAMILY PARENTING PATTERNS OF ISLAMIC RELIGIOUS EDUCATION TEACHERS AT KALIAWI WAY KANAN ELEMENTARY SCHOOL - Solihin; Annisah, Siti (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
The family is the primary educational environment for the formation of children's values and character. Islamic Religious Education teachers hold a strategic position because they play a dual role as formal educators at school and role models of religious and social values within the family. This study aims to analyze the process of internalizing religious and social values in the parenting patterns of Islamic Religious Education teachers' families in Negeri Besar District, Way Kanan. The study used a descriptive qualitative approach with 12 purposively selected families of Islamic Religious Education teachers as subjects. Data were collected through in-depth interviews, non-participatory observation, and documentation studies, then analyzed using the Miles and Huberman interactive model. The results show that internalization of religious values is carried out through the habit of routine worship, moral education based on the dalil (theoretical principle), and consistent parental role models. Meanwhile, social values are internalized through children's active involvement in community activities, concrete practices of social concern, and reflective dialogue to foster empathy. The dominant parenting style is democratic-authoritative parenting with a foundation of Islamic values, characterized by two-way communication and clear yet flexible rules. This finding confirms that a professional background as an Islamic Religious Education teacher is an important cultural asset in forming structured parenting strategies, even though it still faces contemporary challenges such as the influence of digital technology and parents' limited time.